Graduate doctors' rural work increases over time. (2nd September 2019) - Playford, Denese; Ngo, Hanh; Atkinson, David; Puddey, Ian B.
Abstract: Background: The contribution of rural clinical school (RCS) and rural origin to developing a long-term rural medical workforce was examined. Methods: Longitudinal cohort study, after undergraduate location in either rural or urban setting, for all medical graduates 2004–2010, identified in the Australian Health Practitioner Regulation Agency, in the following groups: Urban origin/no RCS; Rural origin/no RCS; Urban origin/RCS; and Rural origin/RCS. Results: Proportions of all graduates working rurally increased from 2013 to 2018, including amongst urban origin/nonRCS graduates. Rural origin/RCS participants worked rurally at the highest rates across all time points, with an endpoint of 47%, and an odds ratio of 9.70 (5.41, 17.40) relative to the urban reference group. They had a cumulative duration of rural practice over 5 times higher than the urban reference group. RCS graduates were more likely to be working in remote areas than nonRCS graduates. Conclusion: All graduates' contribution to rural and remote workforce is dynamic and increasing. Both RCS participation and rural student recruitment make synergistic and increasing contributions to rural work. RCS effects workforce distribution to more remote areas. Single cross-sectional studies do not capture this dynamic growth in the rural workforce.